Characteristics of Balinese architectural flats in Denpasar city - I Putu Suta Suyasa; Parwata I Wayan; Mahaputra I Nyoman Gede (Master Program of Infrastructure and Environmental Engineering, Postgraduate Program, Warmadewa University, 2023)
The construction of flats can be a solution to the increasing need for houses in the Province of Bali and the depleting land area of residential areas. The existence of demands for flats by prioritizing the architectural requirements of buildings according to the Regional Regulation of the Province of Bali Number 5 of 2005 is a unique thing to study. The aim of the research is to find the factors that influence the characteristics of flats with Balinese architecture and to plan a design model for flats in Bali based on the concept of Balinese architecture. This study uses a combination research method model which combines quantitative and qualitative research methods sequentially. In the first stage it was carried out using quantitative research methods and in the second stage used qualitative methods. Sampling using non-probability random sampling, with the sampling convention sampling technique, where the sample selection is free with a sample of 200 respondents. The data analysis technique in this study was univariate analysis by presenting tables, pictures and graphs. The results of the study show that the factors influencing the characteristics of flats with Balinese architecture are the principles of spatial planning with the selection of locations in Denpasar city, the principles of building layout with a 3-storey apartment building height and the selection of building facades in Balinese architectural style, the principles of utilities and facilities with the presence of green open spaces. , elevator facilities, traditional and cultural facilities, vehicle parking facilities centered in one place, merchant facilities, health and education that are easily accessible, as well as an integrated and organized waste treatment system, as well as the principles of Balinese architecture, namely based on Tri Hita Karana and Hulu Teben concept. The design model for flats is designed with a type 36 residential type which facilitates the majority of families with 1-2 children.